Social signatures in echolocation calls of a leaf-roosting bat, Kerivoula furva. Issue 4 (3rd July 2020) - Kao, Mei-Ting; Liu, Jian-Nan; Cheng, Hsi-Chi; Nakazawa, Takefumi
ABSTRACT: Bats may use echolocation for social communication (e.g. group cohesion and individual recognition) although it has evolved primarily for orientation and foraging. This idea has been tested by using bats living in permanent roosts (e.g. caves) in large colonies. Here, we investigated social signatures in echolocation calls of a leaf-roosting bat, Kerivoula furva, which forms a small-sized group (2–10 individuals), roosts in furled banana leaves and switches roosts almost every day following foliation, but nevertheless, its group membership is largely fixed. We hypothesised that echolocation calls of K. furva differ significantly between groups and/or individuals, so that individuals can effectively find roost members, despite frequently changing roosts. Social structural and call analyses supported this hypothesis. Discriminant function analysis provided correct classifications significantly better than random ones, with 34.8% vs. 25% and 26.5% vs. 6.25% for group and individual signatures, respectively. Taken together with previous studies, our results suggest the possibility that, irrespective of the roost type, echolocation calls of bats generally contain enough information to be potentially useful for social communication. Future studies are encouraged to accumulate individual call data for a standardized comparison of context-dependent call signatures and to better understand social communication of bats.